0918 Amiloride treatment ameliorates MRI surrogate markers of neurodegeneration in primary progressive multiple sclerosis. Issue 3 (9th February 2012) - Arun, T; Sbdarella, E; Ruiter, M; Tomassini, V; Leite, M I; Craner, M; Fugger, L; Jenkinson, M; Palace, J
Abstract : Neurodegeneration is a major substrate for permanent disability in multiple sclerosis (MS) yet current therapies target predominantly inflammatory mechanisms resulting in an unmet need for effective neuroprotective agents. Converging basic science suggests that acid sensing ion channel blockade with amiloride is neuroprotective in animal MS models. In this longitudinal pilot study we assess the potential neuroprotective efficacy of amiloride in MS using MRI surrogates. Seventeen patients with primary progressive MS participated in a pretreatment (1 yr) and amiloride treatment phase (1 yr). Structural MRI and diffusion tensor imaging were performed to assess whole brain atrophy and neuroaxonal integrity. Our results demonstrate amiloride significantly improves corpus callosum radial diffusivity (RD; measures myelin integrity) (21%, p<0.05) changes compared to pre treatment. The amiloride phase also demonstrated a significant reduction in mean diffusivity (MD; measure structural integrity) changes within the deep grey matter (thalamus) compared to pretreatment (58%, p<0.01). This was parallelled by a significant reduction in the whole brain atrophy rate in the post-amiloride phase compared to the pretreatment phase (p=0.009). This translational study strongly supports a role for the further testing of amiloride as a novel neuroprotective drug in the treatment of MS.